Iontophoretic cobalt staining of the body wall of Phocanema decipiens - Bradley, C (Journal of nematology, 1978)
Iontophoretic cobalt staining of the nematode Phocanema decipiens results in the deposition of cobalt between the contractile bases of adjacent muscle cells and in a hexagonal lattice pattern in the hypodermis. The possibility of staining sarcolemmal invaginations between muscle cells which are proprioceptive or coordinate the activity of adjacent muscle cells is suggested